Development of security in wireless sensor network using IPv6 - Jayapal, Vikneswary (2009)
The Wireless Sensor Networks (WSNs) is one of core technologies expected to become a potential basis of future ever-present networks. WSN consists of multiple low cost sensor nodes, which could either, have a fixed location or randomly deployed that can communicate with each other for monitoring environments, medical systems, home network, industry automation and so on. However, most of the application scenarios require connectivity between WSNs and the Internet. Though WSN is typically not IP-enabled, connection to the IP network makes it easy to monitor sensors everywhere in the world. One of the purposes of the research work is to incorporate the IPv6 with WSNs, where IPv6 offers a larger address space. Therefore each of the sensor nodes will have their own IP address compare to IPv4, which has limited address space.The main objective of this research is to implement security in WSNs. Sensor networks are typically characterized by limited power supplies, low bandwidth, small memory sizes and limited energy. In addition, unlike traditional networks, sensor nodes are often deployed in accessible areas, presenting the added risk of physical attack. This leads to a very demanding environment in providing security. The research proposed XOR encryption algorithm that possesses built-in and enhanced security measure. The encryption and decryption of the payload secure the data's of the packet transfer. Other than that the XOR encryption is meant to realize the real time routing where the packets will be delivered within their end-to-end deadlines.XOR encryption security has been implemented in the 61owpan/IPv6 stack for TinyOS 2.1. TinyOS 2.1 an embedded operating system commonly used in wireless sensor networks. The hardware platforms used in this project, the TelosB motes, the 802.15.4 wireless communication standard and the TinyOS 2.1 operating system